2023
DOI: 10.1186/s12967-023-03891-4
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging a cuproptosis-based signature to predict the prognosis and drug sensitivity of cutaneous melanoma

Abstract: Immunotherapy is a vital treatment for patients with cutaneous melanoma (CM), but effective predictors to guide clinical immunotherapy are lacking. Cuproptosis is a newly discovered mode of cell death related to tumorigenesis. Exploring the relationship between the mode of cuproptosis and the effect of immunotherapy on CM could better guide clinical management. We clustered all patients with CM in the Cancer Genome Atlas (TCGA) database based on cuproptosis-related genes (CRGs). Prognosis, immunotherapeutic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The study by Rodríguez et al provided insights into the mechanism governing the function of CD + T cells and DCs in the antitumor response, and they discovered that advanced stage III and IV melanoma had considerably lower densities of cDC1s and CD8 T cells [48]. There is other study that has also observed reduced tumorin ltrating CD8 + T cell values in SKCM patients [49]. This study's results on immune in ltration analysis align with those of Yang et al, who found decreased CD8 + T-cell in ltration of the high risk group in colorectal cancer patients [50].…”
Section: Discussionmentioning
confidence: 99%
“…The study by Rodríguez et al provided insights into the mechanism governing the function of CD + T cells and DCs in the antitumor response, and they discovered that advanced stage III and IV melanoma had considerably lower densities of cDC1s and CD8 T cells [48]. There is other study that has also observed reduced tumorin ltrating CD8 + T cell values in SKCM patients [49]. This study's results on immune in ltration analysis align with those of Yang et al, who found decreased CD8 + T-cell in ltration of the high risk group in colorectal cancer patients [50].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression level of a single gene may be affected by multiple factors, which may lead to unreliable prognostic prediction results of a single gene as an independent prognostic factor (Huang et al, 2021). Furthermore, previous studies have demonstrated the ability of multiple genes to effectively predict outcomes in melanoma patients (Xu et al, 2022;Liu et al, 2023). Consequently, our study then screened six OS-associated genes (IL-18, SEMA6A, PAEP, TNFRSF17, AIM2, and CXCL10) to establish risk score.…”
Section: Discussionmentioning
confidence: 99%
“…These studies show the potential of cuproptosis as a promising research area for understanding the disease, although it is still poorly known in BRCA. Recent attempts have been made to construct CRG signatures to predict tumor prognosis and develop novel and effective treatments [17]. Copper ion carriers and chelators have the potential to be effective therapeutic options for tumor treatment, according to several research [18].…”
Section: Introductionmentioning
confidence: 99%